2016
DOI: 10.1016/j.imlet.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 from marginal zone precursor B cells controls the differentiation of Th17, Tfh and Tfr cells in transplantation tolerance

Abstract: B cells are known to control CD4 T cell differentiation in secondary lymphoid tissues. We hypothesized that IL-10 expression by marginal zone precursor (MZP) regulatory B cells controls the differentiation and positioning of effector and regulatory T cells during tolerization. Costimulatory blockade with donor-specific transfusion (DST) and anti-CD40L mAb in C57BL/6 mice induced tolerance to allogeneic cardiac allograft. B cell depletion or IL-10 deficiency in B cells prevented tolerance, resulting in decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 60 publications
0
57
0
Order By: Relevance
“…IL-10 was increased only in the MZP B cells that up-regulated IL-21R in tolerant recipients, and that were able to promote graft acceptance in B cell-specific IL-10-deficient recipients. These IL-10-producing MZP B cells controlled the differentiation and position of Th17, Tfh and Tfr cells in secondary lymphoid tissues [46], thus providing contrasting mechanistic insights to previous studies on B regs , and underscoring the diversity in phenotype of IL-10-producing B cells that promote transplantation tolerance. Similarly, Durand et al [47] reported that splenic B cells from rats tolerant to allogeneic hearts were enriched for a CD24 int CD38 1 CD27 1 IgD -IgM 1/low regulatory subpopulation that expressed granzyme B and interferon regulatory factor 4 (Irf4) as well as inhibitory CD23 and BANK1.…”
Section: Regulatory B Cells As Mediators Of Tolerancementioning
confidence: 85%
See 1 more Smart Citation
“…IL-10 was increased only in the MZP B cells that up-regulated IL-21R in tolerant recipients, and that were able to promote graft acceptance in B cell-specific IL-10-deficient recipients. These IL-10-producing MZP B cells controlled the differentiation and position of Th17, Tfh and Tfr cells in secondary lymphoid tissues [46], thus providing contrasting mechanistic insights to previous studies on B regs , and underscoring the diversity in phenotype of IL-10-producing B cells that promote transplantation tolerance. Similarly, Durand et al [47] reported that splenic B cells from rats tolerant to allogeneic hearts were enriched for a CD24 int CD38 1 CD27 1 IgD -IgM 1/low regulatory subpopulation that expressed granzyme B and interferon regulatory factor 4 (Irf4) as well as inhibitory CD23 and BANK1.…”
Section: Regulatory B Cells As Mediators Of Tolerancementioning
confidence: 85%
“…IL‐10 was increased only in the MZP B cells that up‐regulated IL‐21R in tolerant recipients, and that were able to promote graft acceptance in B cell‐specific IL‐10‐deficient recipients. These IL‐10‐producing MZP B cells controlled the differentiation and position of Th17, Tfh and Tfr cells in secondary lymphoid tissues , thus providing contrasting mechanistic insights to previous studies on B regs , and underscoring the diversity in phenotype of IL‐10‐producing B cells that promote transplantation tolerance. Similarly, Durand et al .…”
Section: Regulatory B Cells As Mediators Of Tolerancementioning
confidence: 88%
“…Neointimal proliferation and immune infiltration are characteristics of chronic vascular rejection, a process that leads to significant loss of transplanted organ function and may account for decreased long-term graft survival [1][2][3][4]13]. IL-10 is an extensive immune regulator that downregulates the expression of Th1 cytokines, MHC class II antigens, and co-stimulatory molecules on macrophages [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that a single intramuscular administration of type 1 adeno-associated viral vector carrying interleukin-10 gene (AAV1-IL-10) increased systemic IL-10, inhibited neointimal proliferation of aortic allograft and prolonged allograft survival in rat models of aortic and kidney transplantation [12]. IL-10 from marginal zone precursor B cells controls the differentiation of Th17,follicular regulatory CD4+ T cells and follicular helper CD4+ T cells in transplantation tolerance [13]. However, many data suggest IL-10 also mediates immunostimulatory properties [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…In mice models, multiple studies show that Breg can induce Treg and are capable of transferring tolerance in allogeneic cardiac allograft [75], islet allograft [76], and arthritis [77] models. These studies point out the central role of IL-10 in the modulation of the immune response.…”
Section: Breg As Cell Therapymentioning
confidence: 99%